(untitled) (PIONIR: JURNAL PENDIDIKAN, 2022)
This classroom action research aims to improve the ability of prospective teacher students in making learning implementation plans through the learning model of better teaching and learning with character. This research was conducted in four stages, namely planning, implementation, observation, and reflection and was carried out in two cycles. The first cycle carried out by the researcher was observing student competence in making lesson plans. The results of the observation on the assessment of the learning implementation plan in the first cycle showed an average value of 74.2% with a good category. Furthermore, the average value of students in the second cycle increased by 87% in the very good category. The improvement of students’ ability in making lesson plans for each cycle has increased significantly. This proves that the character of the better teaching and learning learning model is able to improve the competence of prospective teacher students in preparing learning implementation plans.